PENINGKATAN NILAI PRODUK PADA KELOMPOK USAHA KECIL PENGEPUL BARANG BEKAS DI KECAMATAN AMBULU DAN KECAMATAN JENGGAWAH KABUPATEN JEMBER - Dodi Setiabudi; Hentihu M Fahrur Rozy (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2018)
Waste is waste that is caused by human activities and consumption. Garbage has become an old problem faced by cities in Indonesia, including the town of Jember. The small business group BAROKAH and FAIQ JAYA are small business groups engaged in the collection of used goods (waste) in the Ambulu and Jenggawah Districts of Jember Regency, which consist of garbage collectors. The types of used products that are accommodated are non-organic waste such as scrap metal, waste/paper, and plastic waste, where the plastic trash and other garbage are collected, and recycling processes can still increase the selling value. This activity aims to increase the value of selling products, income, and knowledge of small business groups as activity partners. The plan for this activity is carried out by holding a plastic garbage crusher, a special cart of chemical, organic waste, and training activities in waste management, garbage utilization training, operational training tools, and equipment maintenance training. The method of implementing this activity is field observation, socialization, discussion with activity partners, designing and manufacturing tools (plastic garbage crusher and organic / non-organic carts, waste management training, waste utilization training, operational training tools, tool maintenance training, and monitoring evaluation of activities. From this activity 1 (one) unit of plastic waste crushing machine has been produced to increase the selling value of plastic waste, 2 (two) groups of organic / non-organic waste bins to streamline the garbage collection process, the activity partners have received training-training waste management, waste utilization training, operational training tools, and tool maintenance training, so that knowledge of increasing product selling value and partner income can increase. Keywords: Plastic Waste